How do healthcare consumers process and evaluate comparative healthcare information? A qualitative study using cognitive interviews - Delnoij Diana MJ; Rademakers Jany; Hendriks Michelle; Damman Olga C; Groenewegen Peter P (BMC, 2009)
Abstract Background To date, online public healthcare reports have not been effectively used by consumers. Therefore, we qualitatively examined how healthcare consumers process and evaluate comparative healthcare information on the Internet. Methods Using semi-structured cognitive interviews, interviewees (n = 20) were asked to think aloud and answer questions, as they were prompted with three Dutch web pages providing comparative healthcare information. Results We identified twelve themes from consumers' thoughts and evaluations. These themes were categorized under four important areas of interest: (1) a response to the design; (2) a response to the information content; (3) the use of the information, and (4) the purpose of the information. Conclusion Several barriers to an effective use of comparative healthcare information were identified, such as too much information and the ambiguity of terms presented on websites. Particularly important for future research is the question of how comparative healthcare information can be integrated with alternative information, such as patient reviews on the Internet. Furthermore, the readability of quality of care concepts is an issue that needs further attention, both from websites and communication experts.